A Study of Noun-Deriving Suffixes in Competition in Middle English - Laura, Esteban-Segura (Miscelánea: A Journal of English and American Studies, 2018)
This paper presents a corpus-driven analysis of the Germanic suffixes -dom, -hood, -lac, -ness, -rede(n), and -ship in Middle English. The main objective is to assess the occurrence and use of synonymous derivations in the corpora examined, namely the Middle English Grammar Corpus (MEG-C) (Stenroos et al. 2014) and the Middle English Local Documents Corpus (MELD) (Stenroos and Thengs 2014). The six suffixes could be attached to the same base with no apparent distinction in meaning, giving way to competing abstract formations. The analysis can shed light and offer fresh insight into the co-occurrence of these contending formations in different Middle English text types, including specialised and more general texts, and help explain their survival or demise.